INTRODUCING AN EFFECTIVE NANOCATALYTIC FOR THE ONE-POT SYNTHESIS AND INVESTIGATION OF BIOLOGICAL PROPERTIES OF PYRANOPYRIMIDINONE AND XANTHENE DERIVATIVES - Pourshamsian, khalil; Amininia, Ali; Sadeghi, Babak (Journal of the Chilean Chemical Society, 2019)
In this study, an effective method for the synthesis of pyranopyrimidinone and xanthene derivatives is introduced. In this method, zinc oxide-chitosan nanocomposite has been used as a catalyst and all reactions were performed under irradiated in a microwave oven at a power of 230W. The properties of zinc oxide-chitosan nanocomposite were characterized by X-ray diffraction (XRD), energy dispersive X-ray (EDAX) analysis and scanning electron microscopy (SEM). The results indicated that the size of zinc oxide-chitosan nanocomposite varies between 76–95 nm. The catalyst activity has maintained its activity after four runs. The main advantages of this method are; Eco-friendly procedure, catalytic synthesis of affordable and inexpensive materials, short reaction time, and excellent yields which makes it more economic than the other conventional methods. The antibacterial activity of the products was investigated using Minimum Inhibitory Concentration (MIC) and the Minimum Bactericidal Concentration (MBC) methods. Pyranopyrimidinone derivatives exhibit more antibacterial activity.